The Combination of Gastrodin and Gallic Acid Synergistically Attenuates AngII-Induced Apoptosis and Inflammation via Regulation of Sphingolipid Metabolism - Wang S; Zhu C; Zhang S; Ma S; Li B; Zhao S; Zhang W; Sun Z (Dove Medical Press, 2024)
Shangtao Wang,1 Chenghao Zhu,1 Shurui Zhang,1 Siyu Ma,1 Baoshan Li,1 Shengbo Zhao,2 Wei Zhang,3 Zhirong Sun1 1School of Chinese Materia Medica, Beijing University of Chinese Medicine, Beijing, People's Republic of China; 2Ningqiang Tianma Research Institution Limited Liability Company, Hanzhong, Shaanxi, People's Republic of China; 3Ningqiang County Traditional Chinese Medicinal Industry Development Center, Hanzhong, Shaanxi, People's Republic of ChinaCorrespondence: Zhirong Sun, School of Chinese Materia Medica, Beijing University of Chinese Medicine, Northeast Corner of the Intersection of Yangguang South Street and Baiyang East Road, Fangshan District, Beijing, 102401, People's Republic of China, Email szrbucm67@163.comBackground: Hypertension (HTN) is closely related to endothelial damage. While tianma (TM) and gouqizi (GQZ) have the potential to be effective in the treatment of HTN in traditional Chinese medicine, their main active ingredients and whether its exert synergistic effects and the underlying mechanisms of synergistic effects are still unclear.Objective: This study screened the active ingredients of TM and GQZ, investigated the synergistic effects of the active ingredients and explored possible mechanisms.Methods: The potential targets and mechanisms of TM and GQZ were screened using network pharmacology, and gastrodin (GAS) and gallic acid (GA) were identified as compounds with significant antihypertensive activity. The synergistic effects of the combination of GAS and GA was assessed by measuring biomarkers of AngII-induced human umbilical vein endothelial cell (HUVECs) dysfunction model. Furthermore, the anti-apoptotic and anti-inflammatory effects were evaluated by measuring inflammatory cytokine secretion, and apoptosis-related markers. Finally, key targets of the sphingolipid signaling pathway were experimentally validated by Western blotting.Results: In network pharmacology, the herb-pair exerted a synergetic effect by regulating sphingolipid pathways. The GAS and GA exerted synergistic protective effects in AngII-induced HUVECs injury by improving Nitric Oxide Content (NO) levels, alleviating lactate Endothelin-1 (ET-1), and Thromboxane B2 (TX-B2) release, reducing the secretion of inflammatory factors like interleukin-6 (IL-6), interleukin-1β (IL-1β), Tumor Necrosis Factor Alpha (TNF-α)), decreasing the pro-apoptotic protein BAX, and increasing the anti-apoptotic protein BCL-2. Furthermore, the results showed that the GAS and GA combination could elevate the level of S1PR1 and inhibit the expression of ROCK2 and the phosphorylation of NF-κB, which are key targets involved in sphingolipid pathways.Conclusion: Our study revealed that the combination of GAS and GA could suppress inflammation and apoptosis, which are highly correlated with sphingolipid signaling pathways, making it a potential candidate for the treatment of HTN. Keywords: gastrodin, gallic acid, synergistic effects, inflammation, apoptosis, sphingolipid pathways